Effect of adding small applications after verification experiment in a power electronics course - Guopeng Zhao (IET Circuits, Devices and Systems)
Abstract In order to deepen the understanding of power electronics circuits, in this study, a teaching method of adding simple small applications of circuits on the basis of basic verification experiments is proposed. Teachers teach basic principles and applications of circuits, and students conduct basic verification experiments of circuits in the laboratory. Simple application experiments are added after the verification experiments. The full‐bridge DC‐DC converter circuit is taken as an example to carry out practical teaching. After completing the function of the full‐bridge DC‐DC converter circuit, a load of DC motor is used. The full‐bridge DC‐DC converter circuit is used to control the speed of the DC motor so as to realise the simple application of the full‐bridge DC‐DC converter circuit with a motor speed control function. By comparing the experimental realisation rate, the correct rate of thinking questions and the in‐depth understanding of the application theory of two experimental classes, namely the class with simple applications and the class without simple applications, it is shown that the students with simple application experiments improved the correct rate of thinking questions and deepened their understanding of the applications. Compared with the situation in which most students in the class that did not conduct the application experiment did not know the application principle in detail, most students in the class that conducted the application experiment had a deep understanding of the applications. Through the questionnaire survey of students, it is observed that the method proposed in this study could deepen the understanding of circuits and the students had a simple and preliminary understanding of the applications of power electronics technology. It improved students' interest in the course and their practicing ability. The proposed teaching method had a good effect.